Yellow tourism: crime and corruption in the holiday sector - Papathanassis, Alexis; Katsios, Stavros; Dinu, Nicoleta Ramona (Tourism, hospitality & event management, 2019)
This book presents the latest research and novel case studies on crime and corruption in the tourism and hospitality industry. It approaches tourism as both a globalised business impacting the livelihood of millions of people, and a highly challenging field of action for national legislators and law enforcement agencies. The global nature and ubiquity of tourism, as well as the core elements of the holiday experience - such as interactions with unknown environments and places, a care-free mind-set, novelty-seeking behaviour and anonymity - render it highly susceptible to victimisation, crime and corruption. Accordingly, the book addresses a comprehensive set of emerging issues, including: conflict and fraud during holidays; criminal and negligence offences at tourists' expense; exploitation and mistreatment of service workers; deterioration of heritage, cultural and natural resources; and securitisation of tourism. - Part I: CSR, Tourist SAfety & Security -- Part II: Tourism Corruption, Holiday Fraud -- Part III: Systemic Governance and Institutions